The Effect of Moral Disengagement on Bystander’s Behavior in Bullying Among Middle School Students - An, Nguyen Le Que; Linh, Nguyen Thi My; My, Bui Thi Diem; Phuong, Tu Minh; Thu, Tran Thi Le; Thuy, Pham Thi Dieu (VNU Journal of Science: Education Research, 2021)
The aim of the current study was to examine use of moral disengagement among middle school students as bystanders to bullying, as well as the links between four domains of moral disengagement and bystander’s behaviors in bullying episode, including pro-bullying, victim-defending and passive bystanding behavior. Participants included 736 adolescents from the urban area of Hanoi ( M age = 13.69; 53.1% male). According to the main hypotheses, all four domains of moral disengagement were negatively correlated with victim-defending behavior and positively correlated with passive bystanding behavior, whereas only three sets of mechanisms were found to be related to pro-bullying behavior, including minimizing one’s agentive role, consequences distortion, and victim attribution. Linear regression analyses indicated that bystander’s behaviors were predicted by minimizing one’s agentive role. Differences regarding gender and grade were also found. These results highlight the importance of particular moral disengagement sets of mechanisms and have potential implications for prevention tackling bullying.